Grain refinement mechanisms and strength-hardness correlation of ultra-fine grained grade 91 steel processed by equal channel angular extrusion. (May 2019) - Song, Miao; Sun, Cheng; Chen, Youxing; Shang, Zhongxia; Li, Jin; Fan, Zhe; Hartwig, Karl T.; Zhang, Xinghang
Abstract: Ferritic/martensitic grade 91 steel (T91 or P91) is one of the candidate materials for primary and secondary loops in sodium cooled fast reactor. Recently, studies show that equal channel angular extrusion (ECAE) and heat treatment can enhance the strength of T91 from 480 MPa to 1600 MPa. However, a detailed refinement mechanism is yet to be clarified. Furthermore, there is a need to correlate the hardness measurement to tensile test results in T91 steels for nuclear application. Here, we report the grain refinement mechanisms in T91 after extensive microstructural analysis. Packet (a group of martensite with the same habit plane) is identified as an elementary unit for grain refinement. The Vickers hardness correlates well with the ultimate tensile strength, with a fitting ratio of ∼3.24. However, the ratio of Vickers hardness to yield strength is a function of ductility in T91 steels. Highlights: Microstructural characterization and hardness were conducted on three different planes in ECAE deformed Grade 91 steels. Packet (a group of martensite with the same habit plane) is identified as an elementary unit for grain refinement. The Hv correlates well with the σUTS but the ratio of Hv to σy is a function of ductility in TMT Grade 91 steels.